Greenhouse gases, global warming and glacier ice melt in Nepal - Karki, Krishna B. (Journal of Agriculture and Environment, 2007)
Concentration of greenhouse gases has been found increasing over the past centuries. Carbon dioxide (9-26% greenhouse effect), methane (4-9%), and nitrous oxide (3-6%) are the three principal greenhouse gasses though chloroflourocarbon and halon are also included as greenhouse gasses but are in very small greenhouse effect. These gasses are produced both from natural process and anthropogenic activities .Increase of these greenhouse gasses from nature in the atmosphere is mainly from the decomposition of organic matter, nitrification and denitrification of nitrogen including respiration by the plants. Anthropogenic production of carbon dioxide is from burning of fossil fuel whereas for methane livestock and paddy cultivation. Agricultural activities mainly use of mineral fertilizer is responsible for nitrous oxide emission. Increase of these gasses in atmosphere increases temperature that further accelerates evaporation of moisture from the earth’s surface. Increase in water vapor in the atmosphere will further aggravate temperature rise. This increase in atmospheric temperature has direct effect in the melting of glacier ice in Nepalese Himalaya. Melting of ice and increases water volume in the glacier fed rivers and glacier lakes. Rise in water volume beyond its capacity the glacial lakes bursts releasing millions of cubit meters of water and takes million of lives and properties downstream. If this continues there will be no more ice left in the Himalaya and in the long run all the rivers of Nepal will go dry and country will face serious water shortage for drinking, irrigation and other purposes. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 1-7